MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS 1 PADA MATERI PENJUMLAHAN DENGAN MENGGUNAKAN MODEL PROBLEM BASED LEARNING DI SDN BARANG 1 - Fitri Rindi Mulia; Hidayah Budi Qur’aini (STKIP Subang, 2023)
Class action research (CAR) is a research approach aimed at addressing various issues that arise in the classroom environment or learning process. Its goal is to find solutions that can improve these conditions to be more effective and efficient achieving desired outcomes. In this study, class action research used to improve the learning outcomes of first-grade students at SD Negeri Barang 1 in the subject of mathematics, specifically on the topic of addition. In this research used Kurt Lewin's model, which consists of four stages: (1) planning, (2) acting, (3) observing, and (4) reflecting. During the initial observation process, it was found that the learning outcomes of first-grade students at SD Negeri Barang 1 were still very low, with only one student able to achieve the standard grade. The first cycle implementing the class action research, percentage of students who achieved the standard grade reached 54.5%, falling under the high to very high category. The second cycle, which implemented problem-based learning as the instructional model, significant impact are shown on improving student learning outcomes. In the second cycle, 81.8% of students were able to achieve the standard grade, falling under the high to very high category. In second cycle, percentage of students who had not reached the standard grade was 18.2%, categorized as a satisfactory grade. This indicates that the instructional model can have a significant positive impact on student learning outcomes. The use of appropriate learning media based on students' developmental stages and the fulfilling role of the teacher as a facilitator also contributed to the improvement of learning outcomes, engagement, motivation, and enthusiasm of the students